TECHNOLOGY OF FORMING AT THE FUTURE TEACHERS OF SELF-EDUCATION COMPETENCE WITH THE USE OF POTENTIAL OF INFORMATIVE-EDUCATIONAL ENVIRONMENT - Bilousova Л.І.; Kyselyova О.Б. (Journal of Information Technologies in Education (ITE), 2009)
The article is devoted to the issue of modern pedagogical education – to forming at the future teachers of self-education competence in the process of their professional preparation. The structural components of the mentioned competence are determined. Technology of its forming at the students of pedagogical specializations with the use of potential of informative-educational environment is grounded.